Orchid bees as bio-indicators for organic coffee farms in Costa Rica: Does farm size affect their abundance? - Hedström, Ingemar; Denzel, Andrew; Owens, Gareth (Revista de Biología Tropical, 2006)
The potential of Euglossini bees, especially Euglossa, as biological indicators of organic vs non organic coffee farms was studied in Atenas and San Isidro, Alajuela, Costa Rica using 1.8-cineole as lure. Observations were made for three days at each of four farms and complemented with data from a year of obsevations. Orchid bees were in greater abundance in the organic farms (t-Student test). However, lower abundances suggest that an organic farm may be negatively affected by the proximity of non-organic farms, depending on its size and distance. Orchid bees may be indicators of organic coffee farms.